Kepatuhan dan Kesadaran Hukum Personil Polres Kota Palopo - Latif, Kamaruddin; Rahmawati; Abdain (Palita: Journal of Social Religion Research, 2024)
The phenomenon of traffic violations among police officers, especially at Palopo City Police Station, South Sulawesi Province, is an important concern in efforts to improve legal compliance and awareness. This study aims to explore the level of compliance and legal awareness of Palopo City Police personnel and analyze the strategies implemented by the Chief of Police in improving these aspects. The method used is descriptive qualitative with normative and empirical legal approaches. Data were collected through interviews, documentation, and observation, then analyzed using data reduction, data presentation, and conclusion drawing techniques, with data validity testing through triangulation. The results showed that the level of compliance and legal awareness of Palopo Police personnel still needs to be improved. Factors such as lack of legal education, weak organizational culture, and low internal supervision are the main causes of non-compliance. The Palopo Police Chief implemented strategies such as improving legal education and training, strengthening internal supervision, and applying strict and consistent disciplinary sanctions. The novelty of this research lies in the use of dual approaches, namely normative and empirical, in examining the legal behavior of police personnel. In addition, this research develops a strategy model based on strengthening organizational culture, and proposes community involvement in supervision as an innovation to improve accountability. By following these recommendations, it is expected that legal compliance of personnel can increase and public trust in the police institution is maintained.   Keywords: Legal Compliance, Legal Awareness, Police Personnel